Diagnosis and treatment of orofacial pain - Eleni Sarlani (Universidade Estadual de Campinas, 2015)
Orofacial pain is a complex health care problem that may compromise the quality of life of the patient and frustrate the clinician. A variety of disorders may account for the development of pain in the orofacial structures. Temporomandibular disorders are among the most common causes of orofacial pain. Frequently orofacial pain is due to neuropathic, vascular or neurovascular mechanisms. In addition, numerous local pathologies or systemic diseases can result in the development of orofacial pain, while pain in the face may also be referred from a distant structure. Idiopathic and psychogenic types of orofacial pain are also recognized. Establishing a proper diagnosis is the most challenging part of managing orofacial pain and is an essential prerequisite to an effective treatment. A detailed medical history, a thorough evaluation of the patient's complaint and an extensive clinical examination will provide valuable diagnostic information contributing to an accurate diagnosis. This review presents the main diagnostic characteristics and the therapeutic approaches of the most common types of orofacial pain.